Prevalence Of Salivary Secretor Status Of ABO Blood Group Antigens In Potentially Malignant Disorders Of The Oral Cavity (Journal of Pharmaceutical Negative Results, 2022)
INTRODUCTION: In recent times, the salivary secretor status of an individual is increasingly being viewed as a potential contributing factor in the etiopathogenesis of oral precancerous lesions and subsequently cancer. Studies have shown secretor status of an individual is related to the pathogenesis of the disease and have also revealed the association between blood groups and specific diseases. This study aims to assess any association of ABO blood grouping with oral potentially malignant disorders (OPMDs) and to examine whether there is any difference in the saliva secretor status in the patients with OPMDs and healthy controls.MATERIALS AND METHODS: The study included 110 subjects with 55 patients assigned to two groups (a) Patients with potentially malignant disorders (b) healthy control group. Blood samples were collected from all the participants and ABO blood grouping was done. Following this, 1 ml of unstimulated saliva was collected in a sterile test tube and the Wiener agglutination test was performed to analyze the secretor status in both the groups. Chi-square test and Fisher’s exact test was used to assess the relationship between ABO blood group and OPMDs. Chi-square test was performed to assess the relationship between secretor status and OPMDs. The probability value .05 was considered as the significant level.RESULTS: The results of this study revealed that there was neither a statistically significant difference between cases and controls with regard to their salivary secretor status nor between the secretor status of the various blood groups.CONCLUSION: The role of salivary secretor status of ABO blood groups in oral potentially malignant disorders and the importance attached to it as being a contributing factor to oral carcinoma needs to be reconsidered.